Student laboratory manual for physical examination and health assessment - Jarvis, Carolyn (St. Louis, Missouri : Elsevier, Saunders, 2012)
With an easy-to-read approach and unmatched learning support, Physical Examination & Health Assessment, 6th edition offers a clear, logical, and holistic approach to physical exam across the lifespan. Detailed illustrations, summary checklists, and new learning resources ensure that you learn all the skills you need to know.
Unit 1: Assessment of the whole person -- Unit 2: Approach to the clinical setting -- Unit 3: Physical examination -- Unit 4: Integration of the health system.
Keywords: NURSING ASSESSMENT